Investigation of the Electromagnetic Shielding Effectiveness of Needle Punched Nonwoven Fabrics Produced from Stainless Steel and Carbon Fibres - SANCAK, ERHAN; USTA, İSMAİL; YÜKSEK, METİN; ÖZEN, MUSTAFA SABRİ (INST CHEMICAL FIBRES, 2018)
The electromagnetic shielding effectiveness (EMSE) of needle punched, nonwoven fabrics produced using staple stainless steel and carbon fibres was investigated. Utilising carding and large scale industrial type needle punching machines, webs of staple stainless steel and carbon fibres were produced, which were subsequently bonded on the needle punching machine at approximately 132 punches/cm(2) and 13.5 mm needle penetration depth. The effect of varying the carbon fibre content was studied by varying the blend ratio of stainless steel and carbon fibres between 5-20%. EMSE measurements of as-produced needle punched nonwoven fabrics were carried out using the coaxial transmission line method (ASTM D4935-10) in the frequency range of 15-3000 MHz. Within the range, the EMSE values were enhanced from 22.3 dB (95/5, stainless steel/carbon) to 44.7 dB (80/20, stainless steel/carbon), which was attributed to the enhanced conductivity of the fabrics. In fact, the surface resistivity of the samples decreased from 5.80E + 3 Omega to 2.43E + 2 Omega, enhanced for 95: 5 and 80: 20 stainless steel/carbon blends.
Keywords: carbon fibre; electromagnetic shielding; nonwoven; stainless steel fibre; needle punching; WOVEN FABRICS; INTERFERENCE; YARNS; FERRITE